Byzantine Christianity A Very Brief History - Cameron, Averil 1940- (Very Brief Histories, 2017)
Intro -- BYZANTINE CHRISTIANITY -- Contents -- Preface -- Chronology -- Part 1 THE HISTORY -- 1 What was Byzantium? -- 2 Monks, monasteries and bishops -- 3 The age of the Fathers -- 4 The eastern Church splits -- 5 Icons and iconoclasm -- 6 After iconoclasm -- 7 The Macedonian emperors -- 8 Byzantium under the Comneni -- 9 1204 and after -- 10 Byzantium 1261-1453 -- Part 2 THE LEGACY -- 11 Byzantium and Orthodox life and spirituality -- 12 The setting of worship -- 13 Discipline and control -- 14 Orthodox churches and others -- 15 Perspectives today -- Conclusion -- Glossary -- Further reading -- Index.